Truth-Seeking Behavior of Prospective Mathematics Teachers in Solving Islamic-Integrated Problems with Contradictory Information (PWCI): A Mathematical Resilience Perspective - Nanda Dila Zahrotul Khumainah; Achmad Miftachul Ulum; Hanifah Fitriani; Arini Mayan Fa’ani (Edumatika, 2025)
This study aims to describe the truth-seeking behavior of prospective mathematics teachers through the lens of mathematical resilience. This research employs a descriptive qualitative approach. The subjects were prospective mathematics teachers at an Islamic university in Malang, Indonesia, which selected through purposive sampling techniques. Data were collected using questionnaires, tests, and in-depth interviews. The data analysis techniques included data reduction, data presentation, and conclusion drawing/verification. The findings reveal that subjects with high mathematical resilience were able to meet all indicators of truth-seeking, as reflected in their comprehensive mastery of relevant information and their ability to solve problems systematically, even when confronted with contradictory information. Subjects with moderate resilience could only fulfill some indicators, indicating challenges in dealing with complex information. Meanwhile, subjects with low resilience demonstrated success in only a few indicators, highlighting significant difficulties in understanding and analyzing contradictory information. These notable differences emphasize the critical role of mathematical resilience in fostering truth-seeking abilities, particularly when integrating Islamic and mathematical perspectives.